Time-dependent quantum study of the kinetics of the O(3P)+CN(X2+)?CO(X1+)+N(2D) reaction - Gogtas, Fahrettin (Elsevier Science Bv, 2006)
Time-dependent wave packet calculations have been performed for the O + CN -> CO + N reaction. The state-to-state and state-to-all reaction probabilities for total angular momentum J = 0 have been calculated. The probabilities for J > 0 have been estimated from the J = 0 results by using J-shifting approximation based on a capture model. Then, the integral cross-sections and thermal rate constants have been calculated. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Real Wave-Packets; Scattering Calculations; Rate Constants; Nitric-Oxide; Shock-Tube; Cn; Molecules; Oxidation; Dynamics; Clouds